Information theory and dimensions: Enhancing Quantum Mechanics (JOURNAL OF ADVANCES IN PHYSICS, 2015)
This paper seeks to discuss why information theory is so important. What is information, knowledge is interaction of human mind and information, but there is a difference between information theory and knowledge theory. Look into information and particle theory and see how information must have its roots in particle theory. This leads to the concept of spatial dimensions, information density, complexity, particle density, can there be particle complexity, and re-looking at the double slit experiment and quantum tunneling. Information functions/ relations are discussed.